Quality of life of cancer patients at palliative care units in developing countries: systematic review of the published literature - Gayatri, Dwi; Efremov, Ljupcho; Kantelhardt, Eva Johanna; Mikolajczyk, Rafael (Quality of life research, 2021)
Purpose This systematic review aims to summarize factors that influence the quality of life (QOL) of advanced cancer patients in palliative care (PC) in developing countries. Understanding this context in developing countries milieu is necessary; however, this outcome is rarely reported. Methods Following the PRISMA guidelines, the electronic databases MEDLINE, Embase, CINAHL, and Web of Science were systematically searched using the search terms: QOL, cancer, PC, and names of all developing countries. Studies with less than ten subjects, qualitative or pilot studies, reviews, conference abstracts, and that reported validation of QOL questionnaires were excluded. Results Fifty-five studies from 15 developing countries in the African ( n = 5), Latin America and the Caribbean ( n = 10), and Asian ( n = 40) region were included in the narrative synthesis. 65.4% were cross-sectional, 27.3% were cohort studies, 7.3% were RCTs or quasi-experimental studies. Around 30 QOL factors were studied with 20 different types of QOL instruments. Advanced cancer patients who were older, married/ever married, participated in additional care within PC, used complementary and alternative medicine (CAM), and practiced spirituality/religiosity showed higher QOL score. Low educational level and high depression were associated with a lower QOL. Conclusion Various factors affect QOL among cancer patients in PC. Patients valued the use of CAMs; however, the quality and safety aspects should be properly addressed. Important factors that influenced the QOL score were social and spiritual support. While there is a general need to develop PC strategies further, recognizing patients’ needs should be prioritized in national cancer programs.